Pemanfaatan Fitur Instagram Story dalam Membangun Citra Diri Sebagai Warga Negara yang Baik Pada Remaja di Desa Karangduren - Dini Laili Tanika; Ahmad Muhibbin (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2023)
The purpose of this study is to describe the use of the Instagram story feature in building self-image as good citizens among adolescents in Karangduren Village. This type of research is descriptive qualitative research. This research was conducted on adolescents aged 13-20 years in Karangduren village. Data collection techniques in this study used interviews, observation and documentation. The validity of the data using source and technique triangulation. Data analysis techniques use interactive models consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) adolescents take advantage of Instagram stories in terms of fulfilling the need for information knowledge to show self-image as good citizens, namely seeking any information related to the current condition of the State of Indonesia. (2) teenagers take advantage of Instagram stories in terms of meeting social needs to address self-image as good citizens by interacting with fellow Instagram story users such as sharing or viewing various social activities. (3) teenagers take advantage of Instagram stories in terms of tension or can be said to be looking for entertainment that shows self-image as good citizens, namely by doing recreation that begins with a sense of interest when viewing content uploaded in Instagram stories in the form of video clips about Indonesian culture